Impact of Adjacent Facet Joint Osteoarthritis on Adjacent Segment Degeneration after Short-Segment Lateral Lumbar Interbody Fusion for Indirect Decompression: Minimum 5-Year Follow-Up. (22nd August 2022) - Ouchida, Jun; Nakashima, Hiroaki; Kanemura, Tokumi; Satake, Kotaro; Ito, Kenyu; Tsushima, Mikito; Ando, Kei; Machino, Masaaki; Ito, Sadayuki; Segi, Naoki; Morita, Yoshinori; Ode, Yukihito; et al.
Abstract : Purpose . Lumbar fusion combined with lateral lumbar interbody fusion (LLIF) and percutaneous pedicle screws (PPS) is a widely used, minimally invasive surgical treatment, but studies on incidence and risk factors for subsequent adjacent segment degeneration (ASD) are limited. This study was aimed at investigating midterm incidence and reoperation rate of ASD after indirect decompression (IDD) with LLIF and PPS and at clarifying the impact of preexisting adjacent facet osteoarthritis on development of ASD after IDD. Methods . Forty-one patients who underwent short-segment (1- or 2-level) lumbar fusion with LLIF and PPS with a minimum 5-year follow-up were analyzed. Cephalad adjacent facet osteoarthritis was classified as 1 (normal) to 4 (severe) by an established classification system on preoperative CT. ASD was diagnosed with plain radiographs taken preoperatively and up to 5 years postoperatively, and preoperative degree of facet osteoarthritis was compared between the ASD+ group and ASD- group (control). We also divided patients into two groups according to severity of facet degeneration, mild (grades 1-2) group and severe (grades 3-4) group, and investigated ASD-free survival of the groups by the Kaplan-Meier method. Results . The incidence of ASD at 5 years postoperatively was 34.1%, and the reoperation rate for ASD was 4.9%. The degree of preexisting facet joint osteoarthritis was significantly different between the ASD+ and ASD- groups (grade 1/2/3/4: 0/29/64/7% and 29/62/29/10%, P = 0.008 ). Kaplan-Meier analysis showed the severe group to have significantly lower ASD-free survival than the mild group (P = 0.017 ) at 5 years postoperatively. Conclusion . Comparative analysis of the ASD+ versus ASD- group showed preexisting facet joint osteoarthritis to be a risk factor for ASD progression after IDD. Additional longitudinal studies with long-term follow-up are needed to understand the causal relationship between facet joint degeneration and progression of adjacent segment deterioration following IDD.